2016
DOI: 10.1039/c6ob00539j
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective binding of methyl orange dye by cationic water-soluble pillar[5]arenes

Abstract: A new water-soluble pillar[5]arene with an amide fragment and triethylammonium groups was synthesized by our original method of aminolysis of the ester groups. Using UV-spectroscopy, it is shown that cationic pillar[5]arenes are able to selectively form 1 : 1 complexes with some hydrophobic anions: the guests with bulky uncharged or negatively charged substituents hindering entry into the macrocycle cavity. Highly selective binding of the most lipophilic guest, methyl orange dye, in the form of organic anion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…The additional experiment results (see Supplementary Figs S15 and S16) also supported our conclusion that the azobenzene unit was positioned inside the cavity of 2C-WP5A . Recently, an inclusion complex of azo dye and cationic pillar[5]arenes was reported by Stoikov, which is also confirmed that azobenzene unit threaded in the cavity of pillar[5]arene45.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The additional experiment results (see Supplementary Figs S15 and S16) also supported our conclusion that the azobenzene unit was positioned inside the cavity of 2C-WP5A . Recently, an inclusion complex of azo dye and cationic pillar[5]arenes was reported by Stoikov, which is also confirmed that azobenzene unit threaded in the cavity of pillar[5]arene45.…”
Section: Resultsmentioning
confidence: 64%
“…The K a values and thermodynamic parameters are listed in Table 1, and we are surprised to find that there was no obvious difference between the K a - cis and the K a - trans . The hydrophobic interaction is characterized by positive value of ΔH454748, which suggests that the hydrophobic interaction is the main force in the complexation. Meanwhile, 2C-WP5A and G immobilized their conformation during the complexation, resulted in a great negative entropy change which offset the positive entropy change aroused by solvent liberation49.…”
Section: Resultsmentioning
confidence: 99%
“…We previously developed a method [29] for introducing tertiary amino groups into the structure of pillar [5]arene. Diamines containing both primary and tertiary amino groups were used as aminating agents [30].…”
Section: Synthesis Of Decasubstituted Pillar[5]arenes Containing Sulfmentioning
confidence: 99%
“…Further, Stoikov and García‐Río groups demonstrated interactions of water‐soluble cationic pillar[5]arenes with a series of organic sulfonate guests (for example 20 – 24 ). In particular, CP[5]‐5 and CP[5]‐6 showed high selectivity towards azo dye of methyl orange .…”
Section: Molecular Recognition Of Cp[n]smentioning
confidence: 99%
“…Further, Stoikov and García‐Río groups demonstrated interactions of water‐soluble cationic pillar[5]arenes with a series of organic sulfonate guests (for example 20 – 24 ). In particular, CP[5]‐5 and CP[5]‐6 showed high selectivity towards azo dye of methyl orange . The binding stoichiometries and modes between smaller pentamer CP[5]‐2 and larger negatively charged guests 22 – 24 are distinctly different, namely 1 : 1/1 : 2 internal inclusion complexation for 22 , internal/semi‐external binding for 23 , and 1 : 2 external binding for 24…”
Section: Molecular Recognition Of Cp[n]smentioning
confidence: 99%